Cytotoxicity - Aşkin Çelik, Tülay (IntechOpen, 2018)
The book Cytotoxicity is aimed to be an essential reading to all medical students, biologists, biochemists and professionals involved in the field of toxicology. This book is a useful and ideal guide for novice researchers interested in learning research methods to study cytotoxic bioactive compounds. The parts of this book describe the replacement and different applications of the cytotoxic agents. All chapters are written by paramount experts in cytotoxicity research. This will hopefully stimulate more research initiatives, funding, and critical insight into the already increasing demand for cytotoxicity researches that have been evidenced worldwide.